Identification of phytochrome B amino acid residues mutated in three new phyB mutants of Arabidopsis thaliana - Bradley, J; Murphy, G; Whitelam, G; Harberd, N (1996)
The growth and development of plants is regulated by light via the action of photoreceptors which are responsive to the red/far-red, blue and UV regions of the spectrum. Phytochrome B (the apoprotein of which is encoded by the PHYB gene) is one of the red/far-red absorbing photoreceptors active in this process. In this paper, the isolation and characterization of three new EMS-induced mutations of Arabidopsis which confer phytochrome B deficiency are described. Complementation analysis showed that these mutations (phyB- 101, phyB-102 and phyB-104) were allelic with PHYB. DNA sequence analysis showed that all three mutants contain nucleotide substitutions in the PHYB gene sequence. phyB-101 carries a nucleotide substitution within the second exon of the PHYB gene. This G-to-A substitution is a missense mutation that converts a glutamate residue at position 812 of the phytochrome B apoprotein to a lysine residue. phyB-102, another missense mutant, carries a C-to-T substitution which converts a serine residue at position 349 of the phytochrome B apoprotein to a phenylalanine residue. phyB-104 carries a premature stop codon as a result of a G-to-A mutation 1190 bp downstream of the ATG start codon of the PHYB sequence. The missense mutations in phyB-101 and phyB-102 cause significant alterations in the predicted secondary structure of their respective mutant polypeptides, and identify amino acid residues playing crucial roles in phytochrome B function, assembly or stability.